Cognitive function and brain structure after recurrent mild traumatic brain injuries in young-to-middle-aged adults - List, Jonathan; Ott, Stefanie; Bukowski, Martin; Lindenberg, Robert; Flöel, Agnes (Frontiers in Human Neuroscience, 2015)
Recurrent mild traumatic brain injuries (mTBIs) are regarded as an independent risk factor for developing dementia in later life. We here aimed to evaluate associations between recurrent mTBIs, cognition, and grey matter volume and microstructure as revealed by structural magnetic resonance imaging (MRI) in the chronic phase after mTBIs in young adulthood. We enrolled 20 young-to-middle-aged subjects, who reported two or more sports-related mTBIs, with the last mTBI>6 months prior to study enrolment (mTBI group), and 21 age-, sex- and education matched controls with no history of mTBI (control group). All participants received comprehensive neuropsychological testing, and high resolution T1-weighted and diffusion tensor MRI in order to assess cortical thickness (CT) and microstructure, hippocampal volume, and ventricle size. Compared to the control group, subjects of the mTBI group presented with lower CT within the right temporal lobe and left insula using an a priori region of interest approach. Higher number of mTBIs was associated with lower CT in bilateral insula, right middle temporal gyrus and right entorhinal area. Our results suggest persistent detrimental effects of recurrent mTBIs on CT already in young-to-middle-aged adults. If additional structural deterioration occurs during aging, subtle neuropsychological decline may progress to clinically overt dementia earlier than in age-matched controls, a hypothesis to be assessed in future prospective trials.